Innovative Work Management of Teachers of SMA Negeri 1 South Halmahera and SMA AL-Khairaat of Labuha in South Halmahera District (Multi Site Study) - Tjadi, Ridwan La; Rawis, J.A. M.; Londa, Treesje K.; Lengkong, Jeffry S.J. (Asia Pacific Journal of Management and Education (APJME), 2021)
This study aims to find out 1). Innovative work planning for teachers of SMA Negeri 1 of South Halmahera and SMA AL-Khairaat Labuha, 2). The implementation of innovative work of teachers of SMA Negeri 1 Halmahera and SMA Al-Khairaat Labuha, 3). Supervision of innovative work of teachers of SMA Negeri 1 Halmahera and SMA Al-Khairaat Labuha, and 4). The assessment of innovative work of teachers of SMA Negeri 1 Halmahera and SMA Al-Khairaat Labuha. This study used qualitative approach with narrative research method and the research design used was a multi-site study, where first site is SMA Negeri 1 south Halmahera and second site is SMA AL-Khairaat Labuha where the locus located in south Halmahera district. The results showed that 1). The teachers innovative work planning at the two research sites was compiled through a process consisting of two stages, problem identification and alternative problem-solving option. Establishing teachers’ innovative work development plan and applying the principles of deliberation and consensus, 2). The implementation of innovative work of teachers at the two research sites based on the predetermined work plan and is supported by managerial behaviour in the form of providing motivation, communicating face to face and through the electronic medium such as smartphone and supported by teacher behaviour in the form of being committed to achieving innovative work development goal, 3). Supervision of teacher innovative work consists of three types of supervision which include before, during, and after the implementation of the teachers’ innovative work development plan, 4). The assessment of teachers’ innovative work is carried out through an assessment process consisting of three stages of measuring, comparing, and taking managerial action.